Rising tensions: heritage-tourism development and the commodification of “Authentic” culture among the Cham community of Vietnam - Tuyen D. Quang; William B. Noseworthy; Dave Paulson (Cogent Social Sciences, 2022)
This study examines the complexities of cultural-heritage management in Vietnam and the various tensions that arise within initiatives promoting “authentic” versions of cultural practice. In particular, this research investigates local perceptions concerning the commodification of the Cham New Year (Rija Nâgar) at temple-tower complexes, and explores the implications of sacred religious holidays (ngày lễ) that are organized as festival (lễ hội) events. Arranged by local Vietnamese officials, the implementation of these events for tourists contradicts important Cham worldviews, leading to negative perceptions of tourism among community members, and fears that such practices pose irrevocable damage for Cham spirituality and the future of their ancestral heritage. This research underscores the importance of community involvement with respect to decision making in cultural-heritage management, and that heritage tourism in Vietnam, and Southeast Asia more generally, may be dramatically improved with guidance from indigenous voices and local spiritual leaders.